2006
DOI: 10.1007/bf02806475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of population size on the prospect of species survival

Abstract: Abstract:Many recent studies have demonstrated a negative effect of small population size on single plant traits. However, not much is known about the actual consequences of reduced plant performance on the long-term prospect of species survival.I studied the effect of population size on population growth rate and survival probability in the rare perennial herb Scorzonera hispanica occurring in fragmented grasslands. Its performance was measured using several traits related to reproduction in 21 populations ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 52 publications
0
22
1
Order By: Relevance
“…Because many of the environmental characteristics were correlated with each other, we selected only a subset of those that were only weakly correlated and had significant effect in previous studies in the system (Münzbergová , 2004(Münzbergová , , 2006a. This resulted in the following independent variables: aboveground biomass, Beals index, logarithm of population size, Nei's genetic diversity, and allelic richness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because many of the environmental characteristics were correlated with each other, we selected only a subset of those that were only weakly correlated and had significant effect in previous studies in the system (Münzbergová , 2004(Münzbergová , , 2006a. This resulted in the following independent variables: aboveground biomass, Beals index, logarithm of population size, Nei's genetic diversity, and allelic richness.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we used 20 populations that were found in a previous field survey of the landscape, ranging from 10 to 2475 flowering individuals ( Table 1). The same populations were the subjects of a previous study examining performance of the species in the field (Münzbergová , 2006a).…”
Section: Study Species and Study Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not an unusual result: 598 small populations of Scorzonera hispanica in a fragmented 599 landscape of Cehia (Münzbergová 2006), the rupicolous 600 endemic Petrocoptis pseudoviscosa (García 2008) or the 601 peripheral Cypripedium calceolus populations (García 602 et al 2010) also had growth rates not significantly different 603 from unity or not declining, and good chances to persist in 604 the long run. Similarly, the dynamics of Silene regia 605 populations in American prairies were primarily affected 606 by management and only secondarily by size, isolation and 607 genetic diversity (Menges and Dolan 1998).…”
mentioning
confidence: 99%